Frankenstein's dog - Stine, R. L. (New York, NY : Scholastic Inc., 2013)
Kat feels uncomfortable visiting her scientist Uncle Vic Frankenstein because of the rumors about him also she likes his dog Poochie but strange things happen when there is an accident in Vic's lab.
2.2
3-6.
3-6
Keywords: Dogs -- Juvenile fiction; Robots -- Juvenile fiction; Scientists -- Juvenile fiction; Dogs -- Fiction; Horror stories; Robots -- Fiction; Scientists -- Fiction; Dogs -- Fiction; Horror fiction; Robots -- Fiction; Scientists -- Fiction; Horror fiction